Sawn timber and the impact of sustainable forest management practices in Peninsular Malaysia - Abd Wahob, Noraida; Abdul Samad, Abdul Rahim; Othman, Mohd Shahwahid (Forest Research Institute Malaysia, 2018)
This paper examines the economic impact on sawn timber market in Peninsular Malaysia under the scenarios of sustainable forest management (SFM) practices. Autoregressive distributed lag (ARDL) approach test was employed using time-series data from 1980 to 2015, comprising of five scenarios: (1) 24% reduction in harvested area, (2) 25% increase of the domestic price of sawn timber, (3) 47% increase in input cost, (4) incorporated with scenarios (1), (2) & (3) and (5) 10% increase in contribution of forestry and harvesting activities to total gross domestic products (CGDP). The result revealed that the supply and export of sawn timber had a positive impact on SFM. Even though domestic demand was affected by the increase of prices, the value could be used to compensate for the loss volume of timber. These findings are important to policymakers in order for them to reach a benchmark regarding an appropriate method to sustain forest resources. Based on the scenarios imposed under SFM practices, it was found that it is possible to boost sawn timber industry without compromising efforts to sustain and conserve forest resources.